2023
DOI: 10.1002/adom.202202787
|View full text |Cite
|
Sign up to set email alerts
|

Polymer‐Based Circularly Polarized Luminescent Materials

Abstract: Chiral materials capable of generating circularly polarized luminescence (CPL) have gained rapidly growing research interest by virtue of their peculiar photophysical characteristics and far‐reaching applications. Amongst various CPL materials, polymer‐based CPL materials have constituted an important class owing to their abundant types, ease of manufacture, high thermal stability, as well as, tunable properties. The present work reviews the latest advances in constructing polymer‐based CPL materials, which ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 289 publications
0
24
0
Order By: Relevance
“…To achieve C-dots-based CPRTP materials, selecting an appropriate chiral source and building an efficient chirality transfer process from the chiral source to the C-dots are necessary. The stereohelical structure endows chiral helical polymers with a high level chirality and intense optical activity unmatched by small molecules. Interesting phenomena such as the “chiral amplification effect” and “majority rules” further enable chiral helical polymers to become excellent candidates for constructing CPL materials. , In our previous studies, we have prepared CPL-active chiral helical polyacetylenes with high g lum values up to 10 –1 , which proves the feasibility of fabricating CPL materials based on chiral helical polymers . Moreover, we have found that chiral helical polymers can serve as handed-selective fluorescence filters to transform achiral fluorescence into circularly polarized light even in the absence of any covalent bond or noncovalent bond interaction between chiral components and fluorescent components .…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…To achieve C-dots-based CPRTP materials, selecting an appropriate chiral source and building an efficient chirality transfer process from the chiral source to the C-dots are necessary. The stereohelical structure endows chiral helical polymers with a high level chirality and intense optical activity unmatched by small molecules. Interesting phenomena such as the “chiral amplification effect” and “majority rules” further enable chiral helical polymers to become excellent candidates for constructing CPL materials. , In our previous studies, we have prepared CPL-active chiral helical polyacetylenes with high g lum values up to 10 –1 , which proves the feasibility of fabricating CPL materials based on chiral helical polymers . Moreover, we have found that chiral helical polymers can serve as handed-selective fluorescence filters to transform achiral fluorescence into circularly polarized light even in the absence of any covalent bond or noncovalent bond interaction between chiral components and fluorescent components .…”
Section: Introductionmentioning
confidence: 76%
“…50−54 Interesting phenomena such as the "chiral amplification effect" and "majority rules" further enable chiral helical polymers to become excellent candidates for constructing CPL materials. 55,56 In our previous studies, we have prepared CPL-active chiral helical polyacetylenes with high g lum values up to 10 −1 , which proves the feasibility of fabricating CPL materials based on chiral helical polymers. 57 Moreover, we have found that chiral helical polymers can serve as handed-selective fluorescence filters to transform achiral fluorescence into circularly polarized light even in the absence of any covalent bond or noncovalent bond interaction between chiral components and fluorescent components.…”
Section: Introductionmentioning
confidence: 98%
“…The use of polymers in developing intelligent CP-RTP materials can be simply realized through physical mixing or chemical bonding . 25 Ma et al have reported a series of chiral polymers via radical binary copolymerization of acrylamide and chiral binaphthyl derivates, resulting in tuneable acid-base responsive transition CP-RTP (Scheme 3d) 26 The hydrogen bonding cross-linked networks of polyacrylamide and the crosslinked sulfonate ion were found to efficiently inhibit the vibration and rotation of the phosphors, thus promoting CP-RTP in the amorphous state. Similarly, Zhao et al demonstrated the trigger of CP-RTP in a pair of amorphous copolymers with chiral binaphthyl derivates upon introducing the bromine heavy atom.…”
Section: Synlett Account / Synpactsmentioning
confidence: 99%
“…While the quest for high-quality hard materials persists, there has been a surge in interest toward developing multifunctional soft materials. Soft materials may not possess the same level of strength and durability as hard materials, but their dynamic properties offer unique opportunities for the production of versatile advanced devices. Especially, smart soft materials have been designated as the cornerstone of the next generation of advanced devices and digital enhancement technologies. , Liquid crystals (LCs) with their controllable stimulus response and adaptive properties have been widely utilized in optoelectronic devices as one of the most promising soft materials. With the rapid advancement of chiral supramolecular chemistry in the past few decades, an increasing number of studies have focused on excellent circularly polarized luminescence (CPL)-active materials stemming from the regulation of a cholesteric LC (N*-LCs) medium through the rational design of chiral supramolecular self-assembly or co-assembly. , Normally, this kind of chiral self-assembled or co-assembled process can endow outstanding assembly function and give rise to the ordered and regular helical arrangement textures in N*-LCs, which is greatly beneficial to chiral amplification effect and chiral induction ability. More and more reports have demonstrated that N*-LCs can self-assemble as regular helical superstructure textures between chiral inducers and achiral dyes, which can effectively promote the chirality amplification effect of the achiral dyes through the chiral co-assembled process in the LC medium. Therefore, it is of great significance for the rational design of excellent supramolecular self-assembled and co-assembled CPL-active material.…”
Section: Introductionmentioning
confidence: 99%